Effect of carbamazepine on the bone health of people with epilepsy: a systematic review and meta-analysis. Issue 3 (March 2020) - Zhang, Xinyue; Zhong, Rui; Chen, Qingling; Li, Mengmeng; Lin, Weihong; Cui, Li
Importance: Increasing evidence indicates that carbamazepine (CBZ) treatment in people with epilepsy (PWE) has adverse effects on bone health. Objective: We conducted a meta-analysis to investigate the effect of CBZ on the bone health of PWE. Methods: Two independent reviewers systematically searched PubMed and EMBASE for eligible studies. Standard mean deviations (SMDs) with 95% confidence intervals were used as a measure to investigate the effect of CBZ on bone-related outcomes in PWE. Results: Levels of vitamin D (standardized mean difference [SMD]: −0.62, 95% CI: −0.89 to −0.35) and calcium (SMD: −0.38, 95% CI: −0.67 to −0.09) were significantly lower in the CBZ group than controls. Additionally, significantly higher alkaline phosphatase (SMD: 0.67, 95% CI: 0.52–0.82) was observed in patients using CBZ than controls. However, no significant difference in BMD was found between the two groups (SMD: −0.06, 95% CI: −0.55 to 0.43). Conclusion and significance: This study provided evidence that CBZ treatment has a negative effect on bone health in PWE. Clinical implications are that long-term CBZ treatment may not be a good choice for PWE with skeletal diseases or osteoporosis.